Analisis Hasil Belajar Kognitif IPS Semester 2 Siswa Kelas V SD di Masa Pandemi - Sri Nopianti; Iis Nurasiah; Luthfi Hamdani Maula (STKIP Andi Matappa Pangkep, 2021)
This study aims to analyze the cognitive learning outcomes of social studies in the second semester of class V.1 SDN Suryakencana CBM during the pandemic. This research was conducted from January to mid-June, using descriptive qualitative research methods and data analysis techniques using the Miles and Huberman model. The subject of this research is the homeroom teacher of class V.1 SDN Suryakencana CBM. Data collection techniques using semi-structured interviews and documentation. The results of the research that has been done, namely the second semester social studies cognitive learning outcomes obtained by students during the learning process are not all recorded in the list of values. The homeroom teacher of class V.1 SDN Suryakencana CBM only includes test scores per sub-theme, id-semester assessment, and year-end assessment. So that learning 1-6 which took place before the test was held was only limited to practice. The tool used to calculate the social studies cognitive learning outcomes is using Microsoft Excel formulas. Based on the results obtained, all students of class V.1 SDN Suryakencana CBM were declared complete in participating in social studies learning.